Exposiçao à agrotóxicos e câncer - Pluth, Thaís Bremm (2017)
Brazilian agriculture continues to use more and more pesticides. However, at the same time as helping to increase crop yields, they impact human health. Primarily, this work aimed to carry out an integrative review of studies about exposure to pesticides and cancer with a focus on farmers, rural population, pesticide applicators, and rural workers. Secondly, this study described the epidemiological profile of the 10,499 cancer patients diagnosed between 2005 and 2016, under treatment at a High Complexity Oncological Center (CACON) located in an area with high use of pesticides, as well as investigated the relationship between cancer morbidity coefficient and place of residence which was used as a proxy for pesticide exposure. The Medline/Pubmed database was searched and 74 articles were selected to be part of the integrative review. A cross-sectional design was used to describe cancer cases and simple and multilevel linear regression models were used to investigate the relationship between cancer and possible predictive variables. Results of the integrative review showed that several types of pesticides had a significant association with cancer incidence. Through simple linear regression models, it was found that the growth trend of cancer mortality in the period from 2000 to 2015 was higher in the health regions studied (comprising 119 cities) when compared to values of the state of Rio Grande do Sul and Brazil. Results of the multilevel linear regression model showed that cancer incidence was significantly higher among people living in rural areas than in urban areas. In rural areas, the incidence of cancer was significantly higher among men than among women. Since the regions studied are known for their agriculture-based economy, entailing work which is mainly carried out by men, this study suggests that exposure to pesticides may be linked to a higher incidence of cancer in rural men. It is hoped that this study will contribute to and motivate other research related to cancer and pesticides aiming for the prevention of occupational diseases and the monitoring of the health of rural workers.